2014
DOI: 10.1038/ncomms6632
|View full text |Cite
|
Sign up to set email alerts
|

Postmitotic control of sensory area specification during neocortical development

Abstract: The mammalian neocortex is subdivided into cytoarchitectural areas with distinct connectivity, gene expression and neural functions. Areal identity is initially specified by rostrocaudal and mediolateral gene expression gradients in neuroepithelial and radial glial progenitors (the 'protomap'). On further differentiation, distinct sets of gene expression gradients arise in intermediate progenitors and postmitotic neurons, and are necessary to implement areal specification. However, it is still unknown whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 59 publications
8
79
0
Order By: Relevance
“…We also found that COUP-TFI acts on the LMS population expressing SP8 and on the MMS population expressing COUP-TFII. The regulation of COUP-TFI on Sp8 expression has been well documented in the cortex (Alfano et al, 2014b;Borello et al, 2014), and control of COUP-TFI on COUP-TFII expression levels has been recently shown in the hippocampus (Flore et al, 2016). Thus, a similar mechanism in the CGE might limit the cohort of LMS SP8 + cells reaching the cortex, and compensate for the lack of COUP-TFI in the MMS, as previously proposed for the hippocampus, as both COUP-TFs have similar binding sites and could thus compete for the same target genes (Alfano et al, 2014a).…”
Section: Coup-tfi Controls the Rostral But Not The Caudal Migratory Rmentioning
confidence: 99%
“…We also found that COUP-TFI acts on the LMS population expressing SP8 and on the MMS population expressing COUP-TFII. The regulation of COUP-TFI on Sp8 expression has been well documented in the cortex (Alfano et al, 2014b;Borello et al, 2014), and control of COUP-TFI on COUP-TFII expression levels has been recently shown in the hippocampus (Flore et al, 2016). Thus, a similar mechanism in the CGE might limit the cohort of LMS SP8 + cells reaching the cortex, and compensate for the lack of COUP-TFI in the MMS, as previously proposed for the hippocampus, as both COUP-TFs have similar binding sites and could thus compete for the same target genes (Alfano et al, 2014a).…”
Section: Coup-tfi Controls the Rostral But Not The Caudal Migratory Rmentioning
confidence: 99%
“…S6D,D′). To further support the role of COUP-TFI in regulating Cxcr4 expression in progenitors, we used a complementary approach by crossing the Cre-dependent hCOUP-TFI-floxed transgenic line (Alfano et al, 2014b) with Emx1-Cre, thus allowing overexpression of COUP-TFI in all hippocampal progenitors (Fig. 8G-H′).…”
Section: Coup-tfi Modulates Cxcr4 Expression Levels In Progenitors Dumentioning
confidence: 99%
“…To investigate this, the COUP-TFI flox/flox mouse line was crossed to the Nex-Cre mouse, which acts in early differentiating cortical neurons (Alfano et al, 2014b;Goebbels et al, 2006) (Fig. 7A,A′).…”
Section: Postmitotic Inactivation Of Coup-tfi Does Not Alter Dg Growtmentioning
confidence: 99%
See 2 more Smart Citations